Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1471-0528.2010.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A/H1N1 (2009) infection in pregnancy—an Asian perspective

Abstract: The need for hospitalisation was significantly associated with breathlessness and co-morbidity. There was minimal morbidity and no mortality observed. We attribute this to early presentation, diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 16 publications
2
29
2
1
Order By: Relevance
“…These symptoms were all present in the study, consistent with the findings from other studies of pregnant women during the last pandemic [13,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These symptoms were all present in the study, consistent with the findings from other studies of pregnant women during the last pandemic [13,14].…”
Section: Discussionsupporting
confidence: 93%
“…Pregnant women should be considered a high-risk group for developing complications with this viral infection because of a series of physiologic changes that occur during pregnancy [13]. Healthy Table 3 Association between trimester of pregnancy and severe clinical complications and adverse perinatal outcomes a .…”
Section: Discussionmentioning
confidence: 99%
“…Two of the patients who died were either pregnant or in immediate postpartum (day 3 of the postpartum period). Although seasonal influenza is believed to be more dangerous during pregnancy, a recent report from Singapore noted the absence of any mortality from Influenza A/H1N1 in pregnant females [7]. In contrast, a study from California reported an increased risk of death and complications in pregnant females, including those in the immediate postpartum period [8].…”
Section: Discussionmentioning
confidence: 85%
“…The reason may be that pregnant women are on average younger than nonpregnant women [7], and if they have comorbidities, those may be less severe. At any rate, unlike during other pandemics of influenza, previously healthy young people have been severely affected by the 2009 H1N1 influenza [7][8][9].…”
Section: Discussionmentioning
confidence: 98%